Sifat Aljabar Banach Komutatif dan Elemen Identitas pada Kelas D(K) - Malahayati, Malahayati (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2013)
The first Baire class of bounded functions on separable metric spaces K denoted by B1(k). One of the most important subclass of B1(k) is D(K), by D(K) is denoted the class of all functions on K which are differences of bounded semicontinuous functions. In this paper we proved that D(K) is abelian Banach algebra and identity element